A Protocol to Reduce the Risk of Dealing with Misfires - Douglas A. Anderson; William Birch; Rob Farnfield (International Society of Explosives Engineers, 2016)
In the blasting industry, even to the most safety conscious shotfirer, misfires are a constant source of concern. In the United Kingdom, there are two types of misfire, as classified by the Health & Safety Executive. Type A occurs when testing a shot before firing reveals broken continuity that cannot be rectified. However, due to the fact that a majority of quarries use non-electric initiation [i.e. shock tube] that cannot be tested, this type of misfire is very unusual.